RARE TENDON SHEATH GIANT CELL TUMOR OF THE THUMB – CASE REPORT - Karapandјevska, Simona; Atanasov, Nenad; Trajanovski, Aleksandar; Saveski, Aleksandar; Dalipi, Rezeart; Gjorgjieska, Kornelija; Asani, Durim; Todorova, Teodora; Samardjiski, Milan (Македонско друштво на ортопеди и трауматолози = Macedonian Association of Orthopedics and Traumatology, 2022)
Giant cell tumor of the tendon sheath is benign soft tissue tumor. The literature shows it affects people between age of 30 to 50 years with no gender predominance. Giant cell tumor is benign tumor which sometimes has potential to reappear. After radical surgical removal, according to the literature, 15%44% of the patients have recurrence of the tumor on the same location. This type of tumor is usually located on the fingers, and resembles the second most common benign tumor of the hand. In this report we present a surgically treated patient with giant cell tumor of the tendon sheath in the palmar part of the distal phalanx of the right thumb.
РЕТКА ЛОКАЛИЗАЦИЈА НА ТЕТИВЕН ГИГАНТОЦЕЛУЛАРЕН ТУМОР НА ПАЛЕЦОТПРИКАЗ НА СЛУЧАЈ
Keywords: giant cell tumor of the tendon sheath; thumb